Structural and physical investigation of ordered BaO-deficient Ba3PuO6 - van Hattem, Andries; Popa, Karin; Wallez, Gilles; Boshoven, Jacobus; Colineau, Eric; Dahms, Eckhard; Griveau, Jean-Christophe; Hein, Herwin; Walter, Olaf; Schacherl, Bianca; Vitova, Tonya; Dardenne, Kathy; et al. (Communications chemistry, 2025)
Ternary actinide compounds allow for a range of oxidation states and a rich but often not well-known chemistry. Here, a BaO-deficient plutonium-containing perovskite with a composition close to Ba 3 PuO 6 has been obtained via solid state synthesis. The compound was characterised using X-Ray Diffraction from room temperature up to 1473 K, revealing two phase transitions and ordered Ba-deficiency. X-ray Absorption Spectroscopy was performed at the Pu L 3 - and M 5 -edges. The XANES spectrum at the Pu L 3 -edge and the XANES in high-energy resolution mode at the Pu M 5 -edge both indicate a Pu(VI) oxidation state. Despite the rather complex crystallographic unit cell, Extended X-ray Absorption Fine Structure (EXAFS) spectroscopy at the Pu L 3 -edge yields Pu-O distances of 2.01(1) and 2.4(3) Å. The low-temperature heat capacity of Ba 2.875 PuO 5.875 was measured between 5 and 270 K. The heat capacity and standard entropy at 298.15 K were found to be C p = (251 ± 8) J⋅K −1 ⋅mol −1 and S m 0 = ( 318 ± 8 ) J ⋅ K − 1 ⋅ mol − 1 , respectively. The magnetic susceptibility was measured from 2 to 320 K and shows a temperature-independent paramagnetism, consistent with the hexavalent oxidation state of Pu. This article reports the first extended low-temperature heat capacity curve and a temperature-dependent magnetic susceptibility measurement in a [Rn]5 f 2 Pu-based system. The exact crystal chemistry of perovskites containing 5f elements has remained a matter of debate. Here, the authors synthesise a BaO-deficient Pu-based perovskite with a composition close to Ba3PuO6 and study the Pu oxidation state, the crystal structure and Ba/Pu ratio, reporting on thermodynamic and magnetic properties and offering new insights into Ba-Pu-O solid-state chemistry.